2019
DOI: 10.1371/journal.ppat.1007855
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii Type 4B Secretion System-dependent manipulation of endolysosomal maturation is required for bacterial growth

Abstract: Upon host cell infection, the obligate intracellular bacterium Coxiella burnetii resides and multiplies within the Coxiella-Containing Vacuole (CCV). The nascent CCV progresses through the endosomal maturation pathway into a phagolysosome, acquiring endosomal and lysosomal markers, as well as acidic pH and active proteases and hydrolases. Approximately 24-48 hours post infection, heterotypic fusion between the CCV and host endosomes/lysosomes leads to CCV expansion and bacterial replication in the mature CCV. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 94 publications
(144 reference statements)
2
43
0
Order By: Relevance
“…Similar to M. tuberculosis , Neisseria gonorrhoeae PorB, the major outer membrane porin, permits Rab5 to be continuously expressed on the early phagosome, resulting in the blockade of phagosome maturation [ 143 ]. Coxiella burnetii also arrests phagosome maturation by consistently expressing Rab5 on early phagosomes [ 144 ]. Marcelo G Binker et al found that N. gonorrhoeae expresses an IgA1 protease that specifically cleaves LAMP-1 to arrest phagosome maturation [ 145 ].…”
Section: Regulation Of Phagosome Maturation During Microbial Infecmentioning
confidence: 99%
“…Similar to M. tuberculosis , Neisseria gonorrhoeae PorB, the major outer membrane porin, permits Rab5 to be continuously expressed on the early phagosome, resulting in the blockade of phagosome maturation [ 143 ]. Coxiella burnetii also arrests phagosome maturation by consistently expressing Rab5 on early phagosomes [ 144 ]. Marcelo G Binker et al found that N. gonorrhoeae expresses an IgA1 protease that specifically cleaves LAMP-1 to arrest phagosome maturation [ 145 ].…”
Section: Regulation Of Phagosome Maturation During Microbial Infecmentioning
confidence: 99%
“…Specifically, this study showed a correlation of an increase in host cholesterol within the PCV membrane and increases in PCV acidity during later stages of mouse embryonic fibroblast C. burnetii infection [ 56 , 57 ] ( Figure 1 ). Inhibition of bacterial protein synthesis followed by a decrease in sterol recruitment suggests that host sterol composition within the PCV is actively regulated by Coxiella effector proteins, which likely modulate endosomal trafficking and cholesterol acquisition [ 58 , 59 ]. C. burnetii also contains an active sterol reductase, which catalyzes the last step in the cholesterol biosynthesis pathway, implying a possible use of host sterol intermediates for bacterial completion of cholesterol production [ 60 ].…”
Section: Intracellular Bacteria That Replicate Inside a Vacuole Dumentioning
confidence: 99%
“…Additionally, HeLa cells overexpressing the transcription factor EB (TFEB), which coordinates expression of lysosomal genes for lysosomal proteases and hydrolases, led to increased Cts B activity, indicating an increase in the number of proteolyticallyactive lysosomes. TFEB-induced lysosome biogenesis significantly reduced C. burnetii CCV formation and intracellular growth due to acidification and increased protease activity (Samanta et al, 2019). These data underscore the importance of Cts B in the control of C. burnetii intracellularly and present a mechanism where a bacterial intracellular niche is created by regulating the acidity of the vacuoles-containing bacteria and blocking endosomal maturation.…”
Section: Coxiella Burnetiimentioning
confidence: 63%